Production and properties of CsSrBr₃:Eu²⁺ scintillator - Cherginets, V.L.; Grippa, A.Yu.; Rebrova, T.P.; Datsko, Yu.N.; Ponomarenko, T.V.; Rebrova, N.V.; Kosinov, N.N.; Zelenskaya, O.V. (Functional Materials, 2012)
CsSrBr₃ scintillation crystals doped with Eu²⁺ (0.5, 1 and 5 mol. %) have been grown by Bridgman-Stockbarger method. The radioluminescence spectra of CsSrBr₃:Eu²⁺ materials include a narrow band with the maximum which position is shifted from 435 to 442 nm with increase of Eu²⁺ concentration in the growth melt. The light yield of CsSrBr3:Eu2+ material achieves maximal value at 5 mol. % of Eu²⁺ and it is equal to 35 % relative to NaI:TI and the best energetic resolution is 9 %.